THE NEED FOR POWDER CHARACTERISATION IN THE ADDITIVE MANUFACTURING INDUSTRY AND THE ESTABLISHMENT OF A NATIONAL FACILITY - Benson, Jeffrey Malcolm; Snyders, Ettienne (The South African Journal of Industrial Engineering, 2015)
The characteristics of powders used in additive manufacturing can have significant effects on process efficiencies and the quality of the final products. Powder sizes and morphologies need to be optimised for a particular process, and this requires the facilities to perform these measurements as well as provide a quality check on powder batches that are purchased. The establishment of a national powder characterisation facility has been identified by the Titanium Centre of Competence (a DST-funded initiative) as a critical form of support for the development of a South African titanium metal industry. This paper discusses what effect the different powder characteristics can have on the selective laser sintering processes, as well as the state of development of this national facility.